2022
DOI: 10.1158/1538-7445.am2022-3401
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3401: Whole genome cell-free tumor DNA mutational signatures for noninvasive monitoring of pediatric brain cancers

Abstract: Introduction: Liquid biopsy offers a noninvasive approach to monitor cancer burden during therapy and surveillance period. However, in pediatric brain cancers, liquid biopsy methods from the blood have been unsuccessful due to a low tumor burden and low number of mutations in coding regions. We hypothesized that a whole genome sequencing (WGS)-derived patient specific mutational signature from a matched tumor-normal WGS can provide a sensitive and specific approach to detect mutations in circulating cell free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We have previously reported that state-transition models can be used to predict time-sequential transcriptome dynamics and disease evolution in biological systems such as murine acute myeloid leukemia (AML) 9,10,18 . Constructing a state-space to model biological transitions can capture changes produced by genetic, epigenetic, or microenvironmental perturbations on the transcriptome, which simultaneously deregulate multiple biological processes in order to generate a phenotype such as the leukemic transformation observed here [26][27][28][29] . We have previously shown that micro-RNA and protein abundance (proteomic) data can also be used to create a state-space and characterize state-transitions 10,30 .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that state-transition models can be used to predict time-sequential transcriptome dynamics and disease evolution in biological systems such as murine acute myeloid leukemia (AML) 9,10,18 . Constructing a state-space to model biological transitions can capture changes produced by genetic, epigenetic, or microenvironmental perturbations on the transcriptome, which simultaneously deregulate multiple biological processes in order to generate a phenotype such as the leukemic transformation observed here [26][27][28][29] . We have previously shown that micro-RNA and protein abundance (proteomic) data can also be used to create a state-space and characterize state-transitions 10,30 .…”
Section: Discussionmentioning
confidence: 99%